2001
DOI: 10.1289/ehp.01109s3381
|View full text |Cite
|
Sign up to set email alerts
|

Air pollution and respiratory symptoms: results from three panel studies in Bangkok, Thailand.

Abstract: Several studies in North American cities have reported associations between air pollution and respiratory symptoms. Replicating these studies in cities with very different population and weather characteristics is a useful way of addressing uncertainties and strengthening inferences of causality. To this end we examined the responses of three different panels to particulate matter (PM) air pollution in Bangkok, Thailand, a tropical city characterized by a very warm and humid climate. Panels of schoolchildren, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
35
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 9 publications
1
35
0
1
Order By: Relevance
“…Based on the data in Table 1, nearly 84,000 pediatric wheeze-associated disorders events have been investigated to assess the impact of ambient air pollution in five countries. Of these, four studies were conducted in Thailand (7,(41)(42)(43), three in Vietnam (44)(45)(46), and one each in Singapore, Indonesia and Malaysia (8,9,47).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the data in Table 1, nearly 84,000 pediatric wheeze-associated disorders events have been investigated to assess the impact of ambient air pollution in five countries. Of these, four studies were conducted in Thailand (7,(41)(42)(43), three in Vietnam (44)(45)(46), and one each in Singapore, Indonesia and Malaysia (8,9,47).…”
Section: Resultsmentioning
confidence: 99%
“…Eight studies reported the effects of PM 10 (7, 8, 41-44, 46, 47), three reported the effects of PM 2.5 (41,43,46), four studies reported the effects of SO 2 (9,43,44,46), five studies reported the effects of NO 2 (8,9,44,46,47), three reported the effects of CO (8,46,47) and four reported the effects of O 3 (44)(45)(46)(47). Only one study reported the effects of TSP, PM 1 and NO x but Nhung et al (46) presented three estimates for PM 1 and NO x while only one estimate for TSP was given by Chew et al (9), therefore the effects of TSP were analyzed further.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been several studies of ambient PM 10 exposure and risk for upper and lower respiratory Downloaded by [Oregon State University] The OR were calculated for a 10 μg/m 3 and interquartile range increment of particulate matter (and subfractions); adjusted ORs were adjusted for daily weather conditions. -Vadakan et al, 2001) investigated daily upper and lower respiratory symptoms in 3 categories consisting of children, adults, and nurses in relation to daily outdoor PM 2.5 and PM 10 concentrations over 3 mo. A 45-μg/m 3 (approximately interquartile range) change in PM 10 was associated with risk of 1.10 and 1.13, respectively, for UPRD and LWRD in children.…”
Section: Discussionmentioning
confidence: 99%
“…For example, recent reports on air quality and respiratory health indicate that five times more children than adults die from asthma each year in the United States and that in Toronto, Ontario, children experience more than 1,200 acute bronchitis episodes per year as a result of air pollution from traffic sources (U.S. Environmental Protection Agency 2002;Toronto Public Health 2007). Indeed, literature reveals that children bear a disproportionate share of the health consequences of exposure to air pollution, due to their relatively smaller lung surface, their stage of health development, and the proportion of time they spend outdoors (Vichit-Vadakan et al 2001;Neidell 2004).…”
mentioning
confidence: 99%